Automatic Street Light: An automation system as a manifestation of the smart village concept in Secang Village - Antama, Bhilan Rhiyu; Rahmawaty, Penny (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2025)
This community service activity aims to address the issue of street lighting control in Secang Village, Ngombol Subdistrict, Purworejo Regency. The method employed in this activity is the PPE method (Planning, Production, Evaluation). The process begins with analysing and identifying the problem, followed by planning the materials and circuitry. The next stage is the production of the control modules. Finally, the evaluation phase involves four rounds of control module testing: independent testing, field testing 1, field testing 2, and field testing 3.The evaluation is conducted by observing the lighting points where the control modules have been installed. Observations focus on the control module itself, its operation, and the type of lighting used. These observations consider evaluation aspects such as the sensitivity, reliability, and flexibility of the control modules. This activity resulted in the production and installation of six control modules at six lighting points. All installed control modules operated effectively, and all evaluation aspects were successfully met.